Youth Culture and Social Change
XI, 289 p. 2 illus.
Keywords: This book brings together historians, sociologists and social scientists to examine aspects of youth culture. The book’s themes are riots, music and gangs, connecting spectacular expression of youthful disaffection with everyday practices. By so doing, Youth Culture and Social Change maps out new ways of historicizing responses to economic and social change: public unrest and popular culture. .